Analysis of attendances by the Mobile Emergency Service - 192 in Dourados – MS - de Lima, Nilton Fernando; de Souza Campos Santos, Lucas; Jorge Guerreiro, Victor; Christiano Barboza Lollo, Pablo (LAJEC - Latin American Journal of Emergency Care, 2023)
Objective: to analyze the trauma care provided by the Mobile Emergency Care Service in Dourados - MS. Method: retrospective cross-sectional study, in which 3,623 visits were performed between June 2018 and May 2019, observing the variables: sex, age, day of the week, period of the day, nature of the trauma, displaced mobile unit and outcome of the occurrence. Results: the main gender of the victims was male (57.89%), aged between 20 and 39 years (42.28%). The incidents gathered in the weekends (34.94%), in the afternoon (34.41%), with traffic accidents being the main cause of the occurrences (52.77%). The basic support unit was the most used (69.11%) and the predominant outcome was referral to public health units (74.03%). Conclusion: the victims most affected by trauma in Dourados are young men, during the weekends, involved in a traffic accident.